Implementasi Prinsip-Prinsip Pembelajaran dalam Pembelajaran Jarak Jauh melalui Aplikasi Obrolan WhatsApp - Windi Megayanti (INTELEKTIUM, 2021)
This study aims to determine the implementation of learning principles in distance learning through the WhatsApp chat application. The method used in this research is the ex post facto method. This research was conducted on students of the Economic Education Study Program, Faculty of Education and Social Sciences, Indraprasta University, PGRI with a sample of 282 students. The results of this study were as many as 81.9% of students stated that they could pay attention to learning well, 52.5% of students felt motivated when participating in learning, 69.5% of students stated that they were able to actively participate in learning, 62.4% of students stated that they felt involved when learning takes place, 84.8% stated that they could re-access the material that had been studied, 49.3% said the given task could accommodate their understanding, and 54.3% stated that the complexity of learning could be solved through learning via WhatsApp. Based on this research, it can be concluded that learning principles such as attention and motivation, activeness, direct involvement, repetition, challenges, and individual differences have been implemented well even though learning is carried out remotely through the WhatsApp chat application. However, teachers seem to need to pay attention to the challenges and individual differences in the implementation of distance learning through WhatsApp. This can be seen from the results of the study that the task given with the aim of accommodating understanding turned out to be the lowest number, not even reaching 50%. This shows that there is a need for other innovations in an effort to accommodate understanding in order to facilitate each individual who has differences in understanding each material given.